THE EFFECT OF WORK STRESS AND WORK LOAD ON THE WORK PRODUCTIVITY OF EMPLOYEES AT THE REGENCY OF POPULATION AND CIVIL REGISTRATION OFFICES. OGAN KOMERING ULU - Herlina, Tati -; Rabiulkhri, Mailani -; Nevada, Nevada - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
This research discussed the Influence of Work Stress and Workload on Work Productivity of Employees of the Department of Population and Civil Registration Kab. Ogan Komering Ulu. The population in this study were 46 employees of the Department of Population and Civil Registration Kab. Ogan Komering Ulu. The analytical method used was quantitative method using Multiple Linear Regression analysis tool. analysis explained that the t-count of each variable of Work Stress (X1) was -4.342 and Workload (X2) was -3.996 which was greater than the t-table value of 2.017 which stated that all variables had a negative influence on the Work Productivity of the Population and Civil Registration Service employees, Ogan Komering Ulu Regency . The calculated F value of 40,731 was greater than the F table of 3.21 which stated that simultaneously work stress and workload had a negative influence on work productivity of employees of the Population and Civil Registration Office of Kab. Ogan Komering Ulu. The value of the coefficient of determination (R square) of 0.655 meant that in this case the contribution of the influence of work stress and workload had a negative influence on employees'work productivity by 65.5% while the remaining 34.5% was influenced by other variables outside of variables not included in this research model. , such as motivation, discipline, work ethic, skills and education (Sedermayanti, 2011: 214)